APLIKASI SISTEM INVENTORI DAN PENGGAJIAN KARYAWAN PADA PT NOONAKU DESAIN INDONESIA - Andreas Wibowo (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Inventory system application for online shop Noonaku is an application to help the inventory management and provide a brief explanation of what happen in the inventory. The inventory also make a QR code to be scanned later so the worker doesn’t have to be on computer the whole time. Results of testing the QR-Code Scanner has been in line with expectations of the manufacturer of the application, for the dull paper scanner can read the entire laptop up to 100%, while the soiled paper can be read up to 90% of success, and for damaged paper can be read up to 90% success. For testing QR-Code with various sizes can read up 87.5% success. For testing QR-Code with various resolutions can be read up to 80% success.